2012
DOI: 10.3390/jfb3030497
|View full text |Cite
|
Sign up to set email alerts
|

Cell Attachment to Hydrogel-Electrospun Fiber Mat Composite Materials

Abstract: Hydrogels, electrospun fiber mats (EFMs), and their composites have been extensively studied for tissue engineering because of their physical and chemical similarity to native biological systems. However, while chemically similar, hydrogels and electrospun fiber mats display very different topographical features. Here, we examine the influence of surface topography and composition of hydrogels, EFMs, and hydrogel-EFM composites on cell behavior. Materials studied were composed of synthetic poly(ethylene glycol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…The result is shown in Figure 4b. Consistently with the literature (Han et al, 2012), the measured contact angle of untreated PCL electrospun mats was 116 ± 2 , while the PCL fiber mesh after UV irradiation showed slightly lower contact angle of 96 ± 3 . When treated with plasma treatment, the contact angles decreased greatly to 84 ± 3 and 13 ± 1 after 1 and 3 min, respectively.…”
Section: Contact Angle Of Electrospun Matssupporting
confidence: 90%
See 2 more Smart Citations
“…The result is shown in Figure 4b. Consistently with the literature (Han et al, 2012), the measured contact angle of untreated PCL electrospun mats was 116 ± 2 , while the PCL fiber mesh after UV irradiation showed slightly lower contact angle of 96 ± 3 . When treated with plasma treatment, the contact angles decreased greatly to 84 ± 3 and 13 ± 1 after 1 and 3 min, respectively.…”
Section: Contact Angle Of Electrospun Matssupporting
confidence: 90%
“…From a structural perspective, an ideal scaffold should possess interconnected macro pores with sizes from 10 to 100 μm to facilitate cell infiltration and tissue formation, as well as similar topography of natural ECM that would have an impact on cell behavior such as cell adhesion and gene expression (Han et al, 2012;McMurtrey, 2014;Sakai et al, 2008;Sun et al, 2016;Zhang et al, 2014). For that purpose, here we developed a fabrication process to incorporate electrospun short fibers within biopolymer scaffold for tissue engineering applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study used a blend of PCL and gelatin but only reported a compressive strength of about 20 kPa . Synthetically reinforced hydrogel‐ES scaffold composite materials improved cell proliferation, and attachment and spreading of neuroblastoma and rat cortical neuron cells that were attributed to the topography of the ES fibers . We used a different approach to assemble nanofibrous scaffolds into complex architectures by stacking multiple layers of fibers sequentially deposited on top of one another (∼1.5 mm total thickness) for proof‐of‐concept engineering of fiber‐reinforced meniscal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Figures and clearly show the cellular orientations based on the fiber orientation and neurite extensions in the composite matrix respectively. The surface roughness and hydrophilic nature of SA and laminin might contribute to the increased cell–matrix interaction …”
Section: Resultsmentioning
confidence: 99%